Surface Modification of Polydopamine Particles with Polyethyleneimine Brushes for Enhanced Stability and Reduced Fragmentation - Son, Su Hyeon; Kim, Eun Jin; Koo, Hye Young; Choi, Won San (MDPI Open Access Publishing, 2025)
Polydopamine (Pdop) particles possess unique properties but suffer from inherent instability in aqueous environments due to the gradual release of Pdop fragments. This study demonstrated the successful enhancement of the stability and reduction in fragmentation in Pdop particles through surface engineering strategies. Specifically, we investigated the effects of polyelectrolyte multilayer (PEM) coating and polyelectrolyte (PE) brush grafting. Our results showed that PE brush grafting, particularly with long-chain polyethyleneimine (PEI), was more effective in suppressing Pdop fragment release compared to PEM coating. The L-PEI grafted Pdop particles (2.28 chains/nm2) exhibited remarkable stability across a wide pH range (3-9), with inhibition rates exceeding 90% in most cases, reaching 93% at pH 5. Furthermore, a direct correlation between PEI grafting density (0.64 to 2.28 chains/nm2) and inhibition rate was observed, with higher densities yielding greater stability. These findings offer a promising approach for stabilizing Pdop particles for diverse applications.